(untitled) - Christensen, Larry B. (Boston, 2015)
This text provides an understanding of the research methods used to investigate human thought and behavior. The coverage of experimental, qualitative, correlational, and survey research helps students develop their research skills for all aspects of psychology. Information is presented in a simple and straightforward manner and placed into context of actual research studies, helping students make real-life connection.
Keywords: Tâm lý học, thử nghiệm,Psychology, Experimental